Perspektif Sosiologi Mahasiswa PGSD Universitas Muhammadiyah Makassar Terhadap Sistem Perkawinan Bugis Makassar - N, Nurhafsah; N, Nurfita; Sumin, Nurhalisya; Arifin, Jamaluddin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study investigates the viewpoints of PGSD students at Muhammadiyah University Makassar regarding the Bugis-Makassar marriage system from a sociological perspective. Employing a qualitative approach, the research aims to delve into the students' understanding, personal experiences, pros and cons, and expectations concerning the marriage system. Data were collected through in-depth interviews consisting of 21 questions, involving a total of 80 respondents. The results depict a profound understanding of the complexity, allure, and controversies surrounding the Bugis-Makassar marriage system. While students express appreciation for the cultural uniqueness, they also critique specific aspects deemed incompatible with social development. The research findings also reflect variability in students' perspectives on family roles, social norms, and gender issues. In the educational context, students perceive the relevance of understanding the Bugis-Makassar marriage system as a means to cultivate students' awareness of cultural diversity. Their expectations for the Bugis-Makassar marriage system in contemporary times reflect a desire for cultural preservation with adjustments relevant to modern developments and universal values. In conclusion, students convey nuanced perspectives, showcasing an awareness of traditional values while considering changes that can enhance equality and well-being within Bugis-Makassar society.Top of Form